Plasma digoxin levels and ejection fraction in pediatric heart failure - Nafrialdi Nafrialdi; Sake Juli Martina; Mulyadi Djer; Melva Louisa (Indonesian Pediatric Society, 2015)
Background Digoxin has long been prescribed in children with heart failure, but its efficacy has not been evaluated. A previous study at the Department of Child Health, Dr. Cipto Mangunkusumo Hospital revealed that plasma digoxin levels, following a maintenance dose of 15 μg/kg/d, were sub-therapeutic. Regarding its narrow margin of safety, the trend is to use digoxin in even lower dose. Thus, the drug’s impact on cardiac performance need to be evaluated. Objective To evaluate whether a lower maintenance dose of digoxin (10 μg/kg/d) is sufficient to achieve a therapeutic level and to assess for possible correlations between plasma digoxin level and left ventricular ejection fraction (LVEF) as well as fractional shortening (LVFS). Methods A cross-sectional study was conducted on 20 pediatric heart failure patients at the Department of Child Health, Dr. Cipto Mangunkusumo Hospital, Jakarta, from January to May 2012. Plasma digoxin levels were measured by ELISA method after one month or more of treatment; LVEF and LVFS were measured by echocardiography. Correlations between plasma digoxin level and LVEF or LVFS were analyzed by Spearman’s correlation test. The LVEF before and after digoxin treatment were compared by paired T-test. Results Thirteen out of 20 patients had plasma digoxin levels within therapeutic range (0.5-1.5 ng/mL; 95%CI 0.599 to 0.898) and 7 had sub-therapeutic levels (<0.5 ng/ mL; 95%CI 0.252 to 0.417). No significant correlations were observed between plasma digoxin level and LVEF (r=-0.085; P=0.722) or LVFS (r=-0.105; P=0.659). There was a significant increase in LVEF before [42.18 (SD 14.15)%] and after digoxin treatment [57.52 (SD 11.09)%], (P < 0.0001). Conclusion Most patients in this study have plasma digoxin levels within therapeutic range. There are no significant correlations between plasma digoxin level at the time point of measurement and LVEF or LVFS. However, an increase of LVEF is observed in every individual patients following digoxin treatment.